ZAKAT COMMUNITY DEVELOPMENT AS THE KEY OF PRESSING POVERTY NUMBERS IN BANYUASIN REGENCY, SOUTH SUMATERA (MAQASHID SYARIAH APPROACH) - Abdullah Sahroni (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2021)
This research aimed to analize how the effectivity of the zakat on South Sumatra to the mustahik zakat community development throught Maqashid Syariah approachment, the method used in this research was mixed methodology by using data analize inquiries closed which was distributed to respondent with five alternative answers. The result of this research was concluded that, from ZCD program established by BAZNAS indeed having great contribution to evelate prosperity and detract poverty number in Banyuasin has not significant yet, this is because of lack of technics supervision and guidance from BAZNAS side in realizing the program. Meanwhile, through Maqashid Syariah approachment indeed there was an alteration however it is not significant yet, because Teluk Payo society still prioritize how do a living than worhisp regularly.